Ways to Adapt Foreign Fitness Terms in Armenian Language - Saghatelyan, Rita (Bulletin of Yerevan University B: Philology, 2025)
This article explores various methods of full Armenianization and positioning of theterms related to the modern fitness industry within the Armenian language. In thiscontext, we aim to create Armenian equivalents for certain terms based on the generaldevelopment trends of the language. We hope that through consistent and long-termusage, the most effective variants of these terms will become more recognizable.When developing Armenian equivalents for foreign fitness terms, we relied on the Armeniantranslation of terms related to the muscular system and parts of the human body, as theseserve as the foundation of modern fitness vocabulary. In other words, the Armenianequivalents of contemporary fitness terms are primarily based on the precise translation ofEnglish terms related to the human muscular system. Many modern fitness terms originate from English descriptions of various movements,postures, and body positions. Therefore, we paid special attention to accurately translatingthese words into Armenian.In adapting these terms, we employed both calques and semi-calques.We considered another approach to Armenianization of fitness vocabulary – semanticexpansion, as hundreds of colloquial expressions commonly used in fitness have evolved intothe specialized terms over time.We also studied the experience of the Russian language, where, unlike in Armenian, fitnessterminology is already well-established.
Keywords: term; Armenianization of a term; muscular system; calque; semi-calque; semantic neologisms; Armenian equivalent